Awareness of risk management among contractors in the government construction project - Wan Azwanfakhrul, Wan Ibrahim (2018)
Construction industry is one of the biggest industry in the whole world. The contribution of this industry towards the global Gross Domestic Product (GDP) revolves around onetenth of the total amount. Therefore, risk plays an important role in the success of construction project. The problem of delays in the construction industry is a global phenomenon and Malaysia is no exception. Other than that, the tender document is one of the important role to manage risk in construction project progress. This research, therefore, focused on the awareness among contractors in term of tender document. The goals of these research were to study the risk management in construction project, to evaluate awareness of risk management among contractors in the government construction project and to analyze awareness of risk management among contractors in the government construction project. The respondents from various contractor companies and organizations which involved in government project have been approached to get their respond toward the awareness of risk management in construction project by questionnaire distribution. From the survey, the result showed that the awareness among contractors were moderately aware and working progress was the most crucial issue in construction project. Therefore, various contractor companies and organizations need to improve the awareness level in risk management and emphasize this issue to elevate Malaysia into a developed country. The recommendation listed provide further enhancement in awareness of risk management in government construction project.